Icariin prevents oestrogen deficiency–induced alveolar bone loss through promoting osteogenesis via STAT3. (13th January 2020) - Xu, Hongyuan; Zhou, Siru; Qu, Ranyi; Yang, Yiling; Gong, Xinyi; Hong, Yueyang; Jin, Anting; Huang, Xiangru; Dai, Qinggang; Jiang, Lingyong
Abstract: Objectives: Alveolar bone osteoporosis has attracted more and more attention because of its profound impact on stomatognathic function and treatment, but current treatments have not been targeted to alveolar bone and might even cause severe side effects. Thus, identifying the effects of anti‐osteoporosis agents on alveolar bone is essential. Icariin ameliorates metabolic dysfunction of long bones, but its effects on alveolar bone remain unclarified. Materials and methods: BMSCs were isolated from rat mandibles (mBMSCs). The osteogenic potential of mBMSCs and the signalling pathway involved under icariin treatment were measured by ALP and alizarin red staining, reverse transcription‐polymerase chain reaction (RT‐PCR), Western blotting and immunofluorescence. Dual‐luciferase assay, chromatin immunoprecipitation (ChIP) and co‐immunoprecipitation were used to investigate the molecular mechanism. Ovariectomized and sham‐operated rats treated with or without icariin were analysed by micro‐CT, TRAP staining and calcein double labelling. Results: We found that icariin promoted osteoblast differentiation of mBMSCs. Furthermore, STAT3 was critical for icariin‐promoted osteoblast differentiation, as indicated by increased phosphorylation levels in icariin‐treated mBMSCs, while preventing STAT3 activation blocked icariin‐induced osteoblast differentiation. Mechanistically, icariin‐promoted transcription of the downstream osteogenic gene osteocalcin ( Ocn ) through STAT3 and STAT3 bound to the promoter of Ocn . Notably, icariin prevented the alveolar bone osteoporosis induced by oestrogen deficiency through promoting bone formation. Conclusions: For the first time, our work provides evidence supporting the potential application of icariin in promoting osteogenesis and treating alveolar bone osteoporosis.